Criminalization of Terrorist Acts in International Law and Criminal Law: A Comparative Analytical Study (Comprehensive Journal of Science, 2026)
This study examines the criminalization of terrorist acts through a comparative analysis of international and domestic legal frameworks. It focuses on how different legal systems approach the definition and prosecution of terrorism, particularly in light of the absence of a universally accepted definition. This lack of consensus has led to variations in the scope and application of criminalization across jurisdictions.The paper explores the legal foundations underpinning the prohibition of terrorist activities, highlighting the role of international conventions alongside national criminal laws. It also analyzes key forms of terrorist conduct commonly addressed by legislation, including financing, incitement, and participation, while evaluating the effectiveness of the penalties imposed.Furthermore, the study addresses major legal challenges associated with enforcing anti-terrorism laws, such as safeguarding fundamental rights, jurisdictional complexities, and the limitations of international cooperation. By adopting a comparative analytical approach, the research aims to provide a deeper understanding of how legal systems respond to terrorism and to identify gaps that may hinder effective enforcement. Ultimately, it seeks to contribute to the development of more coherent and balanced legal strategies that enhance security while upholding the principles of justice and the rule of law.